Leukocyte susceptibility and immune response against Vibrio parahaemolyticus in Totoaba macdonaldi. (December 2016) - Reyes-Becerril, Martha; Alamillo, Erika; Sánchez-Torres, Luvia; Ascencio-Valle, Felipe; Perez-Urbiola, Juan C.; Angulo, Carlos
Abstract: Vibrio parahaemolyticus is a serious pathogen that affects aquaculture. Nonetheless, to the best of our knowledge, no studies have focused on its immunological implications in Totoaba macdonaldi . Thus, the early immune response to V. parahaemolyticus in juveniles of totoaba was studied at 24 h post-infection with an in vivo study. In addition, changes in cellular innate immune parameters - phagocytosis, respiratory burst activity and viability (annexin V/propidium iodide) - were evaluated in vitro in head-kidney, spleen and thymus leukocytes at 6 and 24 h after bacterial stimulation by flow cytometry. Simultaneously, the expression levels of two immune-relevant genes (IL-1β and IL-8) were measured by using real time PCR. During in vivo study, mRNA transcripts of IL-1β were highly expressed in spleen, thymus and intestine and down-regulated in liver after 24 h post-infection. IL-8 gene expression was upregulated in spleen, intestine and liver compared to that of non-infected fish and down-regulated in thymus after 24 h post-infection. Generally, the results showed a significant decrease in cellular immune responses during the infection, principally in phagocytic ability and respiratory burst. The survival or viability of stimulated leukocytes was significantly reduced causing necrosis and apoptosis, indicating a robust killing response by V. parahaemolyticus . Finally the in vitro analysis showed that transcript levels of IL-1β and IL-8 were up-regulated during stimulation with V. parahaemolyticus in head-kidney, spleen and intestine and down-regulated in thymus at any time of the experiment. Although V. parahaemolyticus has been reported to be an important pathogen for many aquatic organisms, to our knowledge this might be the first report of early-immune response in juvenile totoaba and these immune parameters may be reliable indicators and can be useful in the health control of this species. Graphical abstract: Highlights: Totoaba macdonaldi exposed to Vibrio parahaemolyticus infection showed IL-1β and IL-8 up-regulation in several tissues. In vitro, IL-1β and IL-8 genes in leukocytes exposed to V. parahaemolyticus were up-regulated. The mRNA IL-1β and IL-8 transcription levels were down-regulated in thymus leucocytes exposed to V. parahaemolyticus . Phagocytic and respiratory burst responses during in vitro V. parahaemolyticus stimulation were reduced. The survival of leukocytes exposed to V. parahaemolyticus was reduced, causing apoptosis and necrosis.